Films on African music - Tracey, Andrew (International Library of African Music, 1975)
Films: "Mgodo wa Mkandeni”;"Mgodo wa Mbanguzi";"Mbira: the technique of the Mbira dza Vadzimu”;"Mbira: Mbira dza Vadzimu: religion at the family level”;"Mbira: Mbira dza Vadzimu: urban and rural ceremonies”;"Mbira: Mbira dza Vadzimu: Dambatsoko, an old cult centre”;"Mbira: Njari: Simon Mashoko's traditional and church music”;"Mbira: Matepe dza Mhondoro: a musical healing party”
Keywords: African Music